Emotional blocking in esophageal speech - Williams, William G (Journal of All India Institute of Speech and Hearing, 1971)
Complex as it is for the laryngectomy to produce adequate esophageal speech when all systems function satisfactorily, the process proves even more difficult when emotional blocking occurs. Not only does the withdrawing or overanxious neophyte face this problem but the experienced esophageal speaker also. The following discussion offers a frame of reference that will aid in understanding several aspects of this phenomenon organized under the following headings: (1) The anatomy and neurophysiology of esophageal speech structures, (2) Emotion as a physiopsychological phenomenon, and (3) Implications of emotional blocking in the laryngectomized individual.